Gamification and teaching: the dialogue game as an active and innovative didactic strategy (Research, Society and Development, 2020)
It investigates the contributions of the gamification of the dialogue, in the hermeneutic perspective, and their contributions to education, aiming at the engagement of students, motivating them to open and reflective participation, in the process of promoting active learning. The exploratory and descriptive method was adopted, based on bibliographic research, whose intention was to demonstrate, from the literature and some examples of experiences, the relationship between the hermeneutic dialogue, used as a methodological strategy to awaken the reflective and creative awareness of individuals in the teaching-learning process, and gamification, aimed at engaging and motivating students through the use of mechanics and game-based thinking, offering possibilities for promoting innovative teaching. Finally, it appears that dialogic gamification, as a didactic strategy, puts traditional teaching in question and contributes to the development of active learning.